Disain Dan Implementasi Sistem Penyortir Botol Minuman Otomatis Menggunakan Sensor Berbasis Arduino Uno - Sianturi, Libianko; Sitompul, Inra Ahui; Sihombing, Fiktor; Simanjuntak, Jamser; Hutauruk, Sindak (LPPM Universitas HKBP Nommensen, 2022)
Currently, the goods sorting process in industry still uses a manual method. Therefore, it is necessary to propose an automatic sorting method using control technology. In order to realize the above issue, an automated method is proposed to separate plastic materials and metallic materials in a prototype of goods sorting process. In our study, a plastic bottle and metal bottle detector was designed using a TCRT5000 infrared sensor and an Arduino Uno-based Proximity sensor. The TCRT5000 sensor functions to detect nonmetallic materials while the proximity sensor detects metallic and nonmetallic materials. The sensors will provide logic output to the microcontroller so that the types of materials that enter the sorting system can be distinguished. After the material passes through the sensor, the LCD will automatically display the object value, then the servo motor will sort the objects by moving the actuator to sort the material. Based on the design and implementation of the prototype and based on testing, the plastic bottle material and metal bottle material can be separated properly